Comparative Analysis of the Nodule Transcriptomes of Ceanothus thyrsiflorus (Rhamnaceae, Rosales) and Datisca glomerata (Datiscaceae, Cucurbitales) - Salgado, Marco G.; van Velzen, Robin; Nguyen, Thanh Van; Battenberg, Kai; Berry, Alison M.; Lundin, Daniel; Pawlowski, Katharina (Frontiers in Plant Science, 2018)
Two types of nitrogen-fixing root nodule symbioses are known, rhizobial and actinorhizal symbioses. The latter involve plants of three orders, Fagales, Rosales and Cucurbitales. To understand the diversity of plant symbiotic adaptation, we compared the nodule transcriptomes of Datisca glomerata (Datiscaceae, Cucurbitales) and Ceanothus thyrsiflorus (Rhamnaceae, Rosales); both species are nodulated by members of the uncultured Frankia clade, cluster II.The analysis focused on various features. In both species, the expression of orthologs of legume Nod factor receptor genes was elevated in nodules compared to roots. Since arginine has been postulated as export form of fixed nitrogen from symbiotic Frankia in nodules of D. glomerata, the question was whether the nitrogen metabolism was similar in nodules of C. thyrsiflorus. Analysis of the expression levels of key genes encoding enzymes involved in arginine metabolism revealed up-regulation of arginine catabolism, but no up-regulation of arginine biosynthesis, in nodules compared to roots of D. glomerata, while arginine degradation was not upregulated in nodules of C. thyrsiflorus. This new information corroborated an arginine-based metabolic exchange between host and microsymbiont for D. glomerata, but not for C. thyrsiflorus. Oxygen protection systems for nitrogenase differ dramatically between both species. Analysis of the antioxidant system suggested that the system in the nodules of D. glomerata leads to greater oxidative stress than the one in the nodules of C. thyrsiflorus, while no differences were found for the defense against nitrosative stress. However, induction of nitrite reductase in nodules of C. thyrsiflorus indicated that here, nitrite produced from nitric oxide had to be detoxified. Additional shared features were identified: Genes encoding enzymes involved in thiamine biosynthesis were found to be upregulated in the nodules of both species. Orthologous nodule-specific subtilisin-like proteases that have been linked to the infection process in actinorhizal Fagales, were also upregulated in the nodules of D. glomerata and C. thyrsiflorus. Nodule-specific defensin genes known from actinorhizal Fagales and Cucurbitales, were also found in C. thyrsiflorus. In summary, the results underline the variability of nodule metabolism in different groups of symbiotic plants while pointing at conserved features involved in the infection process.